2020
DOI: 10.3389/fpubh.2020.00108
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Metabolic Health Across Body Mass Index Categories in Central Europe: A Comparison Between Swiss and Czech Populations

Abstract: Comparisons among countries can help to identify opportunities for the reduction of inequalities in cardiometabolic health. The present cross-sectional analysis and meta-analysis aim to address to what extent obesity traits, socioeconomic, and behavioral factors determine poor metabolic health across body mass index (BMI) categories in two urban population-based samples from Central Europe. Data from the CoLaus (∼6,000 participants; Lausanne, Switzerland) and the Kardiovize Brno 2030 (∼2,000 participants; Brno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…Furthermore, Maugeri et al (2020) showed that low income was associated with an increasing number of dietary risk factors for CVD. Kunzova et al (2020) also observed that having low–medium educational level was the main determinant of the metabolically unhealthy profile. These findings suggest that a diet rich in vegetables and fruits may have a beneficial effect in the management of CVD risk factors (Muga et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, Maugeri et al (2020) showed that low income was associated with an increasing number of dietary risk factors for CVD. Kunzova et al (2020) also observed that having low–medium educational level was the main determinant of the metabolically unhealthy profile. These findings suggest that a diet rich in vegetables and fruits may have a beneficial effect in the management of CVD risk factors (Muga et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…In general, low socioeconomic status (SES)—expressed in terms of educational level, employment and income—is associated with earlier onset of age-related chronic diseases and higher risk of death 2 , 3 . Socio-economic disadvantaged individuals tend to fare worse with regards to non-communicable diseases (NCD) risk factors, which include unhealthy behaviors 2 6 . Thus, strategies aiming to reduce health disparities should also include the promotion of healthy behaviors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Underweight individuals, especially men, also had more comorbidities, although not signi cantly [2][3]22]. Similarly, Kunzova et al have found that being male, besides the increasing age, was the main determinant for poor metabolic health regardless of the obesity status [23]. Our results show that respondents with BMI <25 kg/m 2 assess the quality of life as better, they are more satis ed with health in general and are more satis ed with their physical and psychological health, social relations and environment.…”
Section: Discussionmentioning
confidence: 99%